Variabel Kualitas Pelayanan Dan Kinerja Pegawai Pengaruhnya Terhadap Kepuasan Masyarakat Di Desa Wadeng Kecamatan Sidayu Kabupaten Gresik - Ninik Nafsiatul Natasyah; Hadi Sunaryo; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to describe service quality, employee performance, community satisfaction and analyze the effect of service quality, employee performance on community satisfaction in Wadeng Village, Sidayu District, Gresik Regency. This research belongs to the type of explanatory research with a quantitative approach. The method of data collection in this study was done by accidental sampling technique and the distribution of online questionnaires. In determining the number of samples, this study uses the theory of Slovin. The sample used in this study were 65 respondents who were residents of Wadeng Village who provided services from November to December 2021, Petiyin and Brak. To solve the problem in this research, using validity test, reliability test, normality test, classical assumption test, multicollinearity test, heteroscedasticity test, multiple linear regression test, f test, and t test the research uses multiple linear regression analysis with the help of SPSS 21. The results of this study indicate that the Service Quality and Employee Performance Variables have a positive and significant influence on the community.. Keywords: Quality Of Service And Employee Performance Influence On Community Satisfaction